2007
DOI: 10.1016/j.acn.2006.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Practice effects in the prediction of long-term cognitive outcome in three patient samples: A novel prognostic index

Abstract: Practice effects, defined as improvements in cognitive test performance due to repeated exposure to the test materials, have traditionally been viewed as sources of error. However, they might provide useful information for predicting cognitive outcome. The current study used three separate patient samples (older adults with mild cognitive impairments, individuals who were HIV+, individuals with Huntington's disease) to examine the relationship between practice effects and cognitive functioning at a later point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
137
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(150 citation statements)
references
References 21 publications
12
137
1
Order By: Relevance
“…Conversely, individuals with amnestic MCI have been reported to demonstrate practice effects on cognitive and motor tests across brief retest periods (Yan and Dick, 2006;Duff et al, 2007). The equivocal findings in the literature could be attributed to several factors, including small sample sizes (Duff et al, 2007), limited assessment batteries (Cooper et al, 2004;Schrijnemaekers et al, 2006;Yan and Dick, 2006), or long retest periods (Galvin et al, 2005;Schrijnemaekers et al, 2006).…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…Conversely, individuals with amnestic MCI have been reported to demonstrate practice effects on cognitive and motor tests across brief retest periods (Yan and Dick, 2006;Duff et al, 2007). The equivocal findings in the literature could be attributed to several factors, including small sample sizes (Duff et al, 2007), limited assessment batteries (Cooper et al, 2004;Schrijnemaekers et al, 2006;Yan and Dick, 2006), or long retest periods (Galvin et al, 2005;Schrijnemaekers et al, 2006).…”
Section: Introductionmentioning
confidence: 63%
“…Using only one-week data, nearly half of our MCI participants improved so much that they were reclassified as "intact" after one week, whereas the other half retained their MCI status. We have previously suggested that these two subgroups might have differential courses and outcomes (Duff et al, 2007), but this needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the following administration did not show any improvement in the test performance. Although practice effect has been linked as a source of error, earlier study has suggested that it can be a beneficial tool to monitor cognitive status specifically among patients with neurodegenerative disorders at earlier stage (Duff et al 2007). …”
Section: Discussionmentioning
confidence: 99%